Studies on combined effects of graphene oxide-fly ash hybrid on the workability, mechanical performance and pore structures of cementitious grouting under high W/C ratio. (26th April 2021) - Gao, Yuan; Jing, Hongwen; Fu, Guangping; Zhao, Zhenlong; Shi, Xinshuai
Highlights: Fly ash improves the workability of fresh cementitious grouting pastes. GO reinforces the mechanical properties and pore structure of the cement matrix. GO generates hydrated products growth during the hydration of cement. GO-fly ash hybrid promotes the chance to save the cost in grouting projects. Abstract: The superior workability and high early strength of cementitious composites make them have become the most consumed grouting materials in fundamental construction and engineering. However, using cement as grouting materials also brings many issues, such as energy consumption, CO2 emissions, and construction waste production, etc. Here, we real that the industrial by-products fly ash combining with graphene oxide (GO) can be used as a substitute for binder materials to reduce the amount of cement in grouting pastes. The results suggest that fly ash can further improve the workability of grouting materials by reducing the friction effect between the cement particles, and GO can be used to compensate for the loss of mechanical properties caused by fly ash replacing part of the cement powders. 20 wt% fly ash combined with 0.08 wt% GO is proven to be used to effectively replace cement powders of equal weight without influencing the mechanical properties of grouting materials. Microstructure characterization further suggests that GO would not only act as refined templates for the reaction products to grow in cementitious pastes, but also generates as addition nucleation sites into the pore space of fresh binder and promotes more hydration products to grow. The findings of this study promote a great chance to fabricate high performance, lower price, and more environmentally friendly grouting materials in the future.